Why some religious individuals are not emotionally smart? The explanatory role of spirituality - Hui Wen Ng; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2020)
In two studies, we intend to investigate whether spirituality can explain the relationship between intrinsic religious orientation (IRO) and emotional intelligence (EI). Seventy-three worshipping houses-going adults, aged 18-56, had participated in the study. Data was collected by employing Intrinsic Scale of Religious Orientation Scale, Spirituality Assessment Scale, and the Schutte Self-Report Emotional Intelligence Test. Our first study discovered that IRO is not a significant predictor of EI. Nevertheless, Bootstrap analysis with 5000 samples and 95% interval confidence indicated that spirituality fully mediated the link between intrinsic religious orientation and emotional intelligence in our second study. In other words, without high level of spirituality one’s religious orientation does not significantly predict their emotional intelligence. Limitation and suggestion are discussed at the end of the paper.